Vegetation Dispersion, Interspersion, and Landscape Preference - Costa, Marco (Frontiers in Psychology, 2022)
The spatial aggregation/dispersion of the vegetation in a landscape affects landscape texture, with potential important consequences on its perception. The aim of the study was to investigate how plant dispersion and interspersion in small-scale landscapes could affect garden preference. Dispersion referred to proximity and distance between plants, and interspersion referred to the degree of intermixing between plants of different species. Fifty-six participants evaluated 40 pairs of landscapes differing for plant dispersion or plant interspersion. Participants had to rate the preferred landscape in each pair. Furthermore, eye movements during viewing time were recorded, and number of fixations and fixation time were computed for each landscape image. Overall plants arranged in a more dispersed and more interspersed design lead to an increased preference. Dispersion was more effective than interspersion in affecting landscape preference. Number of fixations and fixation total time were higher when viewing landscapes with plants arranged in a high-dispersion, high-interspersion layout.